Use of Stent in Choledochocholedochostomy for Pediatric Liver Transplantation Secondary to Hepatoblastoma: A Case Report - Mauricio Alejandro Saldaña-Ruiz; Mauricio Linnery Rendón-Saldívar; Héctor Fernando Sánchez-Maldonado; Guillermo Alberto Álvarez-Treviño; Federico Ortiz-Alonso (University Library System, University of Pittsburgh, 2023)
BACKGROUND: Hepatoblastoma is a malignant tumor with an insidious clinical presentation, however, it is characterized by an increase in abdominal circumference. In addition, there is PRETEXT staging based on the degree of liver involvement, which ranges from I to IV, of these, for stage IV the treatment of choice is liver transplantation. In addition, the use of stents in the the choledocho - choledochostomy has been tried to reduce post-transplant complications, with variable results. THE CASE: A 18-month-old female with a diagnosis of PRETEXT IV hepatoblastoma and a history of receiving 11 cycles of chemotherapy (CTX) with SIOPEL-3HR scheme, subsequently initiates protocol to receive liver transplantation for being an ideal candidate and PRETEXT IV staging, received from a related living donor. During surgery, it was decided to place a biodegradable stent to perform the choledocho - choledochostomy. She also had hemorrhagic shock grade IV secondary to blood loss, which was successfully resolved. In her first two days post-transplantation she presented adequate flows by Doppler ultrasound and liver enzymes with a downward trend, which remained with the same trend, and she was discharged on day 26 post-transplantation. The following month, she received a cycle of adjuvant CTX with SIOPEL-3HR scheme, without complications. One month later she presented cholestasis and jaundice, so the stent was removed. Currently free of disease, functional graft, and adequate psychomotor development. CONCLUSION: Although the use of a stent was intended to prevent complications such as biliary obstruction, since it is the most feared complication during liver transplantation, this was not the case of the patient, so it could be considered that it continues to be a controversial technique. Also, the use of chemotherapy after transplantation is important to be free of disease since clinical studies have shown an increase in patient survival.